Design and implementation of an identification productivity recording and breeding system for the sheep industry. (2016) - Kontogiannis, Sotirios; Tsipouras, Markos G.; Kokkonis, George; Godas, Dimitrios; Valsamidis, Stavros
This paper presents a new system architecture and test-bed application implementation called sheep manager. Sheep manager system uses near field communication (NFC) technology and custom NFC data exchange format records for the identification and attributes recording of sheep inside a flock. Sheep manager system also utilises sensors for real-time measurements and recording of raw milk extraction per ewe. All recorded information are then stored into an application server following an HTTP representational state transfer protocol specification. The authors also propose an algorithm for sheep breed selection that uses feedback information from past successful breeds in order to increase herd milk productivity.